The moderating effect of corporate governance on corporate social responsibility and information asymmetry: An empirical study of chinese listed companies - Fahd Alduais; Nashat Ali Almasria; Rana Airout (Economies, 2022)
This study is conducted to investigate the relationship between corporate social responsibility (CSR) and information asymmetry (IA), as well as the role of corporate governance (CG) as a moderating factor. This paper employs panel data regression analysis. The CSR disclosure scores are collected from the HX database by way of Hexun.com, while financial data are collected from the CSMAR database. The association between CSR and information asymmetry is examined using generalised least squares (GLS). The current evidence shows that CSR disclosure reduces information asymmetry. In addition, the findings illustrate that particular aspects of CG moderate the relationship between CSR and information asymmetry. More specifically, board size, CEO duality, and board independence positively affect the bid-ask spread. Moderation by the independence board positively affects the relationship between CSR disclosure and information asymmetry. Since the sample is derived from large Chinese companies, the results should be supported by samples obtained from the COVID-19 pandemic in 2020 and, subsequently, comparisons with the entire stock market. In future studies, we recommend conducting research using other variables as proxies regarding information asymmetry. The current study extends existing research on CSR and IA by adding both board characteristics and ownership concentration variables as moderating variables.
Keywords: 330; China; corporate governance; corporate social responsibility; disclosure; information asymmetry